Femtosecond charge transfer dynamics in monomolecular films in the context of molecular electronics - Zharnikov, Michael (Accounts of chemical research, 2020)
Conspectus: A key issue of molecular electronics (ME) is the correlation between the molecular structure and the charge transport properties of the molecular framework. Accordingly, a variety of model and potentially useful molecular systems are designed, to prove a particular function or correlation or to build a prototype device. These studies usually involve the measurements of the static electric conductance properties of individual molecules and their assembles on solid supports. At the same time, information about the dynamics of the charge transport (CT) and transfer in such systems, complementary in the context of ME and of a scientific value on its own, is quite scarce. Among other means, this drawback can be resolved by resonant Auger electron spectroscopy (RAES) in combination with core hole clock (CHC) approach, as described in this Account. The RAES-CHC scheme was applied to a variety of aliphatic and aromatic self-assembled monolayers (SAMs), adsorbed on Au(111) over the thiolate and selenolate docking groups. Electron transfer (ET) from a suitable terminal tail group to the substrate, across the molecular framework, was monitored, triggered by resonant excitation of this group (nitrile in most cases) by narrow-band X-ray radiation. This resulted in the quantitative data for the characteristic ET time, τET, in the femtosecond domain, with the time window ranging from ∼1 fs to ∼120 fs. The derived τET exhibit an exponential dependence on the molecular length, mimicking the behavior of the static conductance and suggesting a common physical basis behind the static CT and ET dynamics. The dynamic decay factors, βET, for the alkyl, oligophenyl, and acene molecular “wires” correlate well with the analogous parameters for the static CT. Both τET and βET values exhibit a distinct dependence on the character of the involved molecular orbital (MO), demonstrating that the efficiency and rate of the CT in molecular assemblies can be controlled by resonant injection of the charge carriers into specific MOs. This dependence as well as a lack of correlation between the molecular tilt and τET represent strong arguments in favor of the generally accepted model of CT across the molecular framework (“through-bond”) in contrast to “through-space” tunneling. Comparison of the SAMs with thiolate and selenolate docking groups suggests that the use of selenolate instead of thiolate does not give any gain in terms of ET dynamics or molecular conductance. Whereas a certain difference in the efficiency of the electronic coupling of thiolate and selenolate to the substrate cannot be completely excluded, this difference is certainly too small to affect the performance of the entire molecule to a noticeable extent. The efficient electronic coupling of the thiolate docking group to the substrate was verified and the decoupling of the electronic subsystems of the substrate and π-conjugated segment by introduction of methylene group into the backbone was demonstrated. No correlation between the molecular dipole or fluorine substitution pattern (at the side positions) and the ET efficiency was recorded. Several representative examples for the resonantly addressable tail groups are given, and perspectives for future research in the context of ET dynamics in molecular assemblies are discussed.
Gesehen am 28.01.2021